Giving Golden Apple Snail Meal Up To 10% of the Ration Can Get Optimal Slaughter Weight, Carcass Weight and Abdominal Fat in Broiler Quail - Endang Sujana; Wiwin Tanwiriah; Opan Suwartapradja; Siti Rabiatul Dinniyah; Adynda Muhammad Fathurrachman (Jurnal Veteriner, 2025)
Quails are a type of poultry that are easy to breed and have advantages such as high egg and meat production, as well as a short and relatively easy in  rearing period.  The research was aimed to evaluate the effect of different levels of Golden apple snail meal (Pomacea canaliculata L.) in the diet on the optimal carcass quality of quail. A total of 100 head of quails were used in this study and were carried out in Sukamenak Village, Darmaraja District, Jatigede, Sumedang Regency of West Java Province. A Completely Randomized Design (CRD) was used to evaluate five treatments (0%, 5%, 10%, 15%, and 20%) Golden apple snail meal on slaughter weight, carcass weight, abdominal fat weight, and edible and inedible weight of meat quails during 42 days of the feeding trial period with four replicates (n=4). The data were statistically analyzed with Analysis of variance (Anova), and if there is a reasonable difference between the treatments, then continue  with Duncan's Multiple Range Test (DMRT) using the statistical analysis system (SAS) application program. The results showed that the inclusion of Golden apple snail meal in the diet significantly (p≤0.05) influenced the slaughter weight, carcass weight, abdominal fat weight, and edible and inedible weight of quails. Based on the findings, it can be concluded that the inclusion of Golden apple snail meal up to 10% in the diet resulted in optimal slaughter weight, carcass weight, abdominal fat weight, and edible and inedible weight of broiler quail.